Judas tree (Cercis siliquastrum L. subsp. siliquastrum) as a possible biomonitor for Cr, Fe and Ni in Istanbul (Turkey) - (:unkn) unknown (My University, 2010)
In this study, leaf (washed and unwashed) and bark samples of Cercis siliquastrum L. subsp. siliquastrum and soil samples collected from 59 different localities, belonged to five stations (urban, urban park, urban roadside, The Bosphorus Coast and the control area) were used to determine heavy metal pollution in Istanbul between 2006-2007 years. In addition, the usability of this plant as a heavy metal pollution monitor to define the pollutant types and to calculate the ratio of airborne and soil borne contaminations in Istanbul was investigated. The Cr, Fe and Ni concentrations of our collected samples were measured by using ICP-OES. The obtained data were analyzed with SPSS statistics program. As a result of the measurements, the average highest and lowest values of heavy metal concentration on the basis of sample locations were as follows: The maximum value of Cr accumulation was gained by bark samples taken from urban park; the value was 6.12±0.59 μg/g dw. The lowest value was detected to be 1.63±0.20 μg/g dw in washed leaf samples from the control area. The highest Fe amount was measured in unwashed leaf samples collected from urban roadside, while the lowest was observed in washed leaf samples from urban area. The values were 134.74±35.06 μg/g dw and 44.97±5.15 μg/g dw, respectively. The average highest Ni value was determined in unwashed leaf samples gathered from urban roadside; the value was 4.47±0.82 μg/g dw. The lowest value was measured in washed leaf samples taken from control area, and this value was determined to be 2.19±0.39 μg/g dw. Our results revealed that Cercis siliquastrum L. subsp. siliquastrum is a useful biomonitor to determine the amount of heavy metal deposits except for Fe. In addition, the tree barks can be used for long-term measurements of heavy metal depositions for this species. © 2010 University of Bucharest.
Keywords: Biomonitor; Cercis siliquastrum; Cr; Fe; ICP-OES; Istanbul; Ni